2017
DOI: 10.1371/journal.pone.0175230
|View full text |Cite
|
Sign up to set email alerts
|

The impact of early visual cortex transcranial magnetic stimulation on visual working memory precision and guess rate

Abstract: Neuroimaging studies have demonstrated that activity patterns in early visual areas predict stimulus properties actively maintained in visual working memory. Yet, the mechanisms by which such information is represented remain largely unknown. In this study, observers remembered the orientations of 4 briefly presented gratings, one in each quadrant of the visual field. A 10Hz Transcranial Magnetic Stimulation (TMS) triplet was applied directly at stimulus offset, or midway through a 2-second delay, targeting ea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 78 publications
4
63
0
Order By: Relevance
“…The null effect of PPC stimulation on the precision parameter is consistent with the observation that brain regions other than the PPC, such as occipital and frontal cortices, also encode sensory representations during the maintenance period of VSTM (Harrison and Tong, 2009;Ester et al, 2013Sprague et al, 2014Sprague et al, , 2016Bettencourt and Xu, 2016;Galeano Weber et al, 2017). In contrast to this null PPC stimulation effect, a recent study has shown that stimulating early visual areas using transcranial magnetic stimulation (TMS) could induce changes in VTSM precision (Rademaker et al, 2017). Differential effects of stimulating the PPC and visual cortex found across our present study and the recent TMS study suggest that these two brain areas may serve differential VSTM functions, as has actively debated in the WM literature (Ester et al, 2015(Ester et al, , 2016 but see Bettencourt and Xu, 2016;Leavitt et al, 2017;Xu, 2017Xu, , 2018Gayet et al, 2018;Scimeca et al, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…The null effect of PPC stimulation on the precision parameter is consistent with the observation that brain regions other than the PPC, such as occipital and frontal cortices, also encode sensory representations during the maintenance period of VSTM (Harrison and Tong, 2009;Ester et al, 2013Sprague et al, 2014Sprague et al, , 2016Bettencourt and Xu, 2016;Galeano Weber et al, 2017). In contrast to this null PPC stimulation effect, a recent study has shown that stimulating early visual areas using transcranial magnetic stimulation (TMS) could induce changes in VTSM precision (Rademaker et al, 2017). Differential effects of stimulating the PPC and visual cortex found across our present study and the recent TMS study suggest that these two brain areas may serve differential VSTM functions, as has actively debated in the WM literature (Ester et al, 2015(Ester et al, , 2016 but see Bettencourt and Xu, 2016;Leavitt et al, 2017;Xu, 2017Xu, , 2018Gayet et al, 2018;Scimeca et al, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…TMS interference during encoding. The effects of TMS interference of the sensory visual cortex activity during the encoding phase of visual information was tested in six experiments, from five studies (Cattaneo, Vecchi, Pascual-Leone, & Silvanto, 2009;Koivisto, Harjuniemi, Railo, Salminen-Vaparanta, & Revonsuo, 2017;Rademaker, van de Ven, Tong, & Sack, 2017;van de Ven, Jacobs, & Sack, 2012;van Lamsweerde, & Johnson, 2017). As expected, the majority of these studies presented evidence supporting the involvement of the sensory visual cortex during VSTM encoding.…”
Section: Systematic Reviewmentioning
confidence: 73%
“…Central to this debate is the sensory recruitment hypothesis, according to which activity in early visual areas is necessary for the successful maintenance of information in VSTM (Harrison, & Tong, 2009;Serences, Ester, Vogel, & Awh, 2009;Supèr, Spekreijse, & Lamme, 2001; for reviews see Pasternak, & Greenlee, 2005;Postle, 2006Postle, , 2015Postle, , 2016Serences, 2016). The sensory recruitment hypothesis is supported by evidence from primate and human studies (e.g., Awh & Jonides, 2001;Christophel et al, 2017;Christophel, Allefeld, Endisch, & Haynes 2018;Harrison, & Tong, 2009;Lorenc, Sreenivasan, Nee, Vandenbroucke, & D'Esposito, 2018;Pasternak, & Greenlee, 2005;Postle, 2006;Rademaker, Chunharas, & Serences, 2019;Serences, 2016;Serences et al, 2009;Sreenivasen, Curtis, & D'Esposito, 2014;Supèr et al, 2001), suggesting that the sensory visual cortex is not only involved in the encoding of visual information, but also in the successful maintenance of it.…”
mentioning
confidence: 99%
“…Repetitive TMS to sensory cortex was found to improve WM precision of nonprivileged (motion) items while impairing precision of privileged (motion) items (Zokaei et al, ), and visual short‐term memory (VSTM) was facilitated for items with an incongruent, subliminal memory mask but impaired for the same items with no memory mask (Silvanto & Soto, ). Rademaker et al () hypothesized, based on their similarly variable findings, that while TMS at 0 ms poststimulus presentation might disrupt early‐phase consolidation in a nontopographic manner, TMS also increases precision of the item at the targeted retinotopic location.…”
Section: Review and Comparison Of Tms Protocols Investigating Workingmentioning
confidence: 99%